Exploring how teacher-related factors relate to student achievement in learning advanced algebra in technology-enhanced classrooms. - Hegedus, Stephen; Tapper, John; Dalton, Sara (Journal of Mathematics Teacher Education, 2016)
In this study, we examine the relationship between contextual variables related to teachers and student performance in Advanced Algebra classrooms in the USA. The data were gathered from a cluster-randomized study on the effects of SimCalc MathWorlds®, a curricular and technological intervention as a replacement for Algebra 2 curriculum, on student learning of Algebra 2 content. Conditional measures (teacher background characteristics) and instructional measures (self-reported instructional preferences, stances, and classroom practices) were subjected to a variety of empirical analyses to discern their relationship to student learning. Researchers examined both the overall effect of teacher contextual variables on student learning and the specific effect of SimCalc on both teacher instructional measures and student performance. There is evidence to support that teachers who use the SimCalc curriculum value classroom communication, deep understanding of math concepts, and support for both routine and non-routine problems. © Springer Science+Business Media Dordrecht 2014.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-412-463-374-521 tex.type: [object Object]
Keywords: Algebra; Connectivity; Dynamic representations; Student achievement; Teacher contextual variables; dept.edu

The impact of technology-enhanced curriculum on learning advanced algebra in US high school classrooms - Hegedus, Stephen J.; Dalton, Sara; Tapper, John R. (Educational Technology Research and Development, 2015)
We report on two large studies conducted in advanced algebra classrooms in the US, which evaluated the effect of replacing traditional algebra 2 curriculum with an integrated suite of dynamic interactive software, wireless networks and technology-enhanced curriculum on student learning. The first study was a cluster randomized trial and the second was a quasi-experimental replication study using a subset of the original treatment teachers. Both studies demonstrated significant impact on student learning of core algebra concepts including both procedural and conceptual problems. Various variables were modeled to understand the impact of such an intervention including demographic factors and class level. We found that being in an honors class significantly predicts learning gains but being in a non-honors SimCalc class significantly predicts learning gains versus all other groups. We also found significant effects of treatment on difference scores for problems which demanded simple procedural approaches and those that demanded complex conceptual understanding.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-090-856-415-345 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Advanced algebra; Classroom connectivity; HLM; Randomized trial; SimCalc; Simulations; dept.edu

Investigating why teachers reported continued use and sharing of an educational innovation after the research has ended - Hegedus, Stephen J.; Dalton, Sara; Roschelle, Jeremy; Penuel, William; Dickey-Kurdziolek, Margaret; Tatar, Deborah (Mathematical Thinking and Learning, 2014)
We investigated prospects for reported sustainable adoption and sharing of an educational innovation through survey research including online questionnaires and telephone interviews. This investigation is part of the Scaling-Up SimCalc experimental program, which combines dynamic representational algebra software (SimCalc MathWorlds) with integrated curriculum and small professional development workshops focused on how to use the software and how to integrate this intervention into the larger year-long curriculum. Teachers who (1) perceived the usefulness of the SimCalc professional development as being consistent with personal aims and (2) perceived specific affordances of the software/curriculum to be valuable were more likely to report continued use of the innovation after the research had ended and that they had shared it with colleagues over time.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-625-976-984-638 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: dept.edu

Uses of technology in upper secondary mathematics education - Hegedus, Stephen; Laborde, Colette; Brady, Corey; Dalton, Sara; Siller, Hans-Stefan; Tabach, Michal; Trgalova, Jana; Moreno-Armella, Luis (Springer, 2017)
Citation Key Alias: lens.org/123-483-507-127-369
Keywords: dept.edu